Gambaran Kadar HbA1c pada Pasien Diabetes Melitus di Rumah Sakit Husada Utama Surabaya - Permatasari, Tika Aprilia; Artanti, Kurnia Dwi (Media Gizi Kesmas, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease characterized by elevated blood glucose levels and can lead to serious health complications if not properly managed. HbA1c measurement is an accurate method for assessing glycemic control over the past 2–3 months and evaluating long-term blood glucose levels. Objectives: To analyze the description of HbA1c levels in patients with DM at Husada Utama Hospital Surabaya. Methods: A descriptive design with a cross-sectional approach was used. The sample consisted of 118 patients with DM who had checked their HbA1c, selected using the accidental sampling method. Secondary data were obtained from the patient's medical records recorded at Husada Utama Hospital. Results: The results showed that 73.7% of the respondents had uncontrolled HbA1c levels (≥6.5%) with an average HbA1c value of 8.18%. The majority of uncontrolled HbA1c levels were found in the elderly (62.1%), female patients (70.1%), patients who had suffered from diabetes mellitus for ≥5 years (57.5%), and those using a combination of oral antidiabetic drugs (39.1%). Conclusion: Based on the findings, it can be concluded that most respondents with uncontrolled HbA1c levels were elderly, female, had been living with DM for ≥5 years, and were using a combination of oral antidiabetic drugs. This indicates that diabetes management still needs improvement.